Sustainable Business Model: MSME System Digitalization and Its Impact on Profitability - Sary, Pritye Lala; Surya, Jen; Rahmi, Rahmi; Imtiman, Syakirah; Amalia, Raudhatul (LPPM STIKI Malang, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the economy in many countries, including Indonesia. MSMEs make significant contributions to job creation, local economies, and social stability. However, many MSMEs face significant challenges in managing supply chains, product distribution, and marketing, which often hinder their growth potential. The digitalization of MSME systems emerges as a solution to address these issues, as technology enables automation, operational efficiency, and expanded market access. This article explores the concept of a sustainable business model that integrates digitalization into MSME operational systems and its impact on profitability. The main focus of this study is on how digital technology can improve efficiency, open new markets, and drive long-term sustainability. By including case analyses, data, and relevant illustrations, this article aims to provide practical insights for MSMEs to optimize their digitalization efforts for higher profitability.